MENUMBUHKEMBANGKAN BUDAYA LITERASI ANAK DI RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) PENJARINGAN INDAH MELALUI GERAKAN LITERASI MASYARAKAT (GELIAT) - Murdiana, Ramdani; Pradipto, Yosef Dedy; Bandur, Agustinus (Universitas Islam Malang, 2024)
Penjaringan RPTRA (Child Friendly Integrated Public Space) experiences limited book stock and lack of ability of RPTRA managers which has an impact on reducing the literacy level of the surrounding community. The Adhiyasa Wirashakti community consisting of Masters and Doctoral students of the LPDP Scholarship (Lembaga Pengelola Dana Pendidikan) PK-212 came and collaborated with the Penjaringan Village of North Jakarta to realize a sustainable Community Literacy Movement (GELIAT). This collaboration involves the community, literacy activists and the government to build a library management system, find problems and support the community to face literacy challenges. This service aims to foster a culture of literacy in the education ecosystem starting from schools, families and communities in the context of learning as an effort to improve the quality of life. The implementation of this program uses the stages of socialization, implementation, and evaluation process through pre-test and post-test. This program was attended by 60 people consisting of the surrounding community and RPTRA administrators. The pre-test results showed a value of 63% and the post-test results showed a value of 84% significantly, this shows that GELIAT activities foster a culture of literacy in the RPTRA community education ecosystem.